Is open science a valid answer to fight against scientific misinformation? - López-Borrull, Alexandre (Anuario ThinkEPI, 2021)
The fight against Covid-19 has also led to the need to fight against scientific disinformation or fake science. Open science as a new paradigm also considers the dissemination of scientific knowledge towards society. This article reflects on whether open science can also be a useful response against misinformation and how this could be achieved.
Keywords: Open science; Misinformation; Disinformation; Fake news; Fake science; Infodemic; Covid-19